2022
DOI: 10.1161/str.53.suppl_1.tp252
|View full text |Cite
|
Sign up to set email alerts
|

Abstract TP252: Intranasal Insulin Treatment Improves Stroke Outcome In Both Male And Female Mice

Abstract: Insulin resistance has been linked to increased risk of stroke recurrence, death, and poor outcome following stroke. Insulin resistance, a common phenomenon following stroke, is associated with elevated levels of insulin circulating in the periphery, which leads to brain insulin deficiency. Brain insulin promotes neuroplasticity and synaptogenesis, has anti-inflammatory, anti-thrombotic, vasodilatory, and anti-apoptotic properties. The impact of brain insulin deficiency and the therapeutic potential of increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…7 Moreover, it was recently shown that the administration of insulin intranasally could treat brain insulin deficiency in high-fat diet-fed insulin-resistant mice as well as improve their post-stroke cognitive function. 8 The biguanide metformin is the first-line glucose-lowering treatment in people with T2D. Its main mechanism of action occurs in the liver with the blocking of gluconeogenesis, but it also acts as an insulin-sensitizer.…”
Section: Type Diabetes Treatments and Their Potential To Improve Post...mentioning
confidence: 99%
“…7 Moreover, it was recently shown that the administration of insulin intranasally could treat brain insulin deficiency in high-fat diet-fed insulin-resistant mice as well as improve their post-stroke cognitive function. 8 The biguanide metformin is the first-line glucose-lowering treatment in people with T2D. Its main mechanism of action occurs in the liver with the blocking of gluconeogenesis, but it also acts as an insulin-sensitizer.…”
Section: Type Diabetes Treatments and Their Potential To Improve Post...mentioning
confidence: 99%